 3x – 5y = 11 x = 3y + 1 Do Now. Homework Solutions 2)2x – 2y = – 6 y = – 2x 2x – 2(– 2x) = – 6 2x + 4x = – 6 6x = – 6 x = – 1y = – 2x y = – 2(– 1) y =

Presentation on theme: "3x – 5y = 11 x = 3y + 1 Do Now. Homework Solutions 2)2x – 2y = – 6 y = – 2x 2x – 2(– 2x) = – 6 2x + 4x = – 6 6x = – 6 x = – 1y = – 2x y = – 2(– 1) y ="— Presentation transcript:

3x – 5y = 11 x = 3y + 1 Do Now

Homework Solutions 2)2x – 2y = – 6 y = – 2x 2x – 2(– 2x) = – 6 2x + 4x = – 6 6x = – 6 x = – 1y = – 2x y = – 2(– 1) y = 2 Solution:(– 1,2)

Homework Solutions 8)2x + 3y = 13 y = 2x – 1 2x + 3(2x – 1) = 13 2x + 6x – 3 = 13 8x – 3 = 13 8x = 16 x = 2y = 2x – 1 y = 2(2) – 1 y = 3 Solution:(2,3)

Homework Solutions 10)3x – 2y = 9 y = 3 – x 3x – 2(3 – x) = 9 3x – 6 + 2x = 9 5x – 6 = 9 5x = 15 x = 3y = 3 – x y = 3 – (3) y = 0 Solution:(3,0)

y = – 2x + 4 x – 5y = 2

3x – 2y = 8 x = –5y – 3

6x – 2y = – 4 y = 3x + 2

Elimination vs. Substitution Use the type of equations you are given to help you determine which method is the better way to solve the system. Elimination is best when neither equation is solved for a variable. Substitution is best when one equation is solved for a variable.

Which method is best? 1)y = 5x 2x + 3y = 34 2) c – 5d = 2 2c + d = 4 3)2x + 3y = 13 5x – 2y = 5 4)7x – 2y = 5 x = 3y – 2

x + 5y = – 3 3x – 2y = 8

c = 5d + 2 2c + d = 4

Download ppt "3x – 5y = 11 x = 3y + 1 Do Now. Homework Solutions 2)2x – 2y = – 6 y = – 2x 2x – 2(– 2x) = – 6 2x + 4x = – 6 6x = – 6 x = – 1y = – 2x y = – 2(– 1) y ="

Similar presentations